A Scaling-up Synthesis from Laboratory Scale to Pilot Scale and to near Commercial Scale for Paste-Glue Production - Sitompul, Johnner P.; Lee, Hyung Woo; Kim, Yook Chan; Chang, Matthew W. (Journal of Engineering and Technological Sciences, 2013)
This paper concerns on developing a synthesis method of paste-glue production for gummed tape using a corn-based starch as an alternative feedstock from laboratory-scale to pilot-scale and to near commercial scale. Basically, two methods of synthesis were developed to produce paste-glue in laboratory scale. Based on the two methods, we then scale-up the earlier laboratory scale data to pilot-scale and near commercial-scale for developing a large scale process production of paste-glue. Scaling up production from 1,000 ml reactor to 500 L pilot-scale reactor and 1,500 L near commercial scale reactor, we monitored pathway of temperature increase during reaction as well as adjustment of operating condition conducted for laboratory experimental data in order to produce a good quality of paste-glue. Some scaling up parameters have been found as well as critical parameters for a good product quality such as viscosity and ceiling temperature of the reaction which are very crucial in order to give optimum operating condition. We have selected synthesis method of paste-glue production and found the range of the parameters in order to produce a very good quality of paste-glue in pilot scale and near commercial scale.